PEMEROLEHAN BAHASA MINANGKABAU PADA ANAK USIA 3-4 TAHUN (TINJAUAN SINTAKSIS) - Redo Andi Marta; Dian Shaumia (Universitas Ahmad Dahlan, 2018)
This study was carried out to produce a single sentence forms in the Minangkabau language acquisition in children 3-4 years of age with Syntax Overview. Forms a single sentence in the Minangkabau language acquisition in children age 3-4 year review based on declarative sentence (statement), interrogative (questions), and imperative (request). Reviews theories used in the study that is the first language acquisition, the forms of a single sentence, the acquisition of syntax in children aged 3-4 years, and Minangkabau language. This article is a review based on a qualitative approach using descriptive method. Source of data used children 3-4 years old female gender. Data in the form of speech, speech writing children aged 3-4 years which contain forms of a single sentence in the form of declarative sentences, interrogative, and imperative. Data collection techniques in this study as follows to record and observe the child who was talking to another friend, a parent, or to the researchers directly. Techniques for data analysis in this study: First, transcribing into the language of the Minangkabau language copy of the tape to the Indonesian language. Second, underline and give code discretion of the child in accordance with the forms of declarative sentences, interrogative, and imperative. Third, interpret or give meaning research results in the form of the sentence forms. Fourth, draw conclusions. Research results in the form of speech, speech delivered by Child Age 3-4 years. In this case informannya natured woman named Tika. Tika in communicating day-to-day use Minangkabau language of their parents, among friends, and the researchers themselves. Speeches delivered in the form of a single sentence in the form of declarative sentences, interrogative sentences and imperative sentences.